A Generalizable Strategy for the 3D Bioprinting of Hydrogels from Nonviscous Photo‐crosslinkable Inks. Issue 8 (16th December 2016) - Ouyang, Liliang; Highley, Christopher B.; Sun, Wei; Burdick, Jason A.
Abstract : An in situ crosslinking strategy is used for 3D bioprinting of nonviscous photo‐crosslinkable hydrogels. This method can be generalized to various photo‐crosslinkable formulations, maintaining high embedded cell viability and tunable cell behavior. Heterogeneous and hollow filaments can be printed using this strategy, allowing fabrication of complex engineered cell‐laden constructs.